2021
DOI: 10.2174/2212798411999201123205022
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Phenolic Compounds Profiles in Tea Extracts and the Composition of these Phenolic Compounds in Yogurt

Abstract: Background:: Green, white, and black tea water extracts are rich in phenolic compounds. Objective:: The changes in phenolic compounds profiles of green, white, and black tea (GT, WT, & BT respectively) water extracts and their respective yogurt were investigated. Method:: Three types of yogurt with tea water extracts were prepared and the phenolic compounds profiles were analyzed using liquid chromatography mass spectrometry (LC-MS) method. Results:: The present data found that flavonol glycosides su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Green tea yogurt, prepared by enriching traditional yogurt with different tea varieties, is gaining popularity as a new functional food [25]. Recent studies have shown that green tea extracts can be successfully incorporated into yogurt, inducing the synthesis of new phenolic compounds and enhancing antioxidant capacity while maintaining the flavor and viability of beneficial microorganisms [26][27][28].…”
Section: Object and Hypothesis Of The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Green tea yogurt, prepared by enriching traditional yogurt with different tea varieties, is gaining popularity as a new functional food [25]. Recent studies have shown that green tea extracts can be successfully incorporated into yogurt, inducing the synthesis of new phenolic compounds and enhancing antioxidant capacity while maintaining the flavor and viability of beneficial microorganisms [26][27][28].…”
Section: Object and Hypothesis Of The Studymentioning
confidence: 99%
“…While the study highlights the potential of combining probiotics and green tea extract to enhance the nutritional value of yogurt, further research is warranted to elucidate the underlying mechanisms and optimize the formulation for practical applications in the food industry. The paper [28] investigates changes in phenolic compound profiles in tea extracts and the composition of these compounds in yogurt. This study elucidates the impact of tea extract addition on the phenolic composition of yogurt and assesses the potential health-promoting properties of phenolic compounds in the final product.…”
Section: Object and Hypothesis Of The Studymentioning
confidence: 99%
“…Similarly, green tea yoghurt, which is prepared by enrichment of traditional yoghurt with different varieties of tea is gaining popularity as a novel functional food (Amirdivani & Baba 2015). Recent studies have shown that green tea extracts can be successfully incorporated into yoghurt which induces the synthesis of new phenolic compounds, and enhance the antioxidant capacity while still maintaining the sensory quality and viability of beneficial microorganisms of raw yoghurt (Mediza Romero et al 2021;Najgebaue-Lejko 2019;Rahmani et al 2021;Shori et al 2021;Świąder et al 2020). Not only green tea, but fermentation with red ginger extract has also been demonstrated to enhance the bioactive potential of yoghurt without negatively affecting the growth of probiotic microorganisms (Larasati et al 2018).…”
Section: Novel Functional Food Products Based On Polyphenolic Ferment...mentioning
confidence: 99%
“…Herbal extracts have been used to fortify dairy products to increase the antioxidant and total phenolic properties of the products. Although this fortification did not seem to affect the quality of the studied products, no organoleptic studies have evaluated the responses of consumers [22,[27][28][29]. In addition, studies have shown that the addition of fruit and vegetable peel extracts to dairy products by microencapsulation improves the nutritional analysis and organoleptic characteristics of the final products [30,31].…”
Section: Introductionmentioning
confidence: 99%